Between hell and tombstone [large type] : where legends are forged in silver and lead ; - Doty, Dennis; Cowan, Amy L.; Wood, Anthony (Saddlebag Dispatches anthologies, 2025)
"From SADDLEBAG DISPTCHES MAGAZINE comes BETWEEN HELL AND TOMBSTONE, a new anthology bringing you the best of the untamed west. Walk down the dusty streets of Tombstone to the O.K. Corral or the Bird cage Theatre. Ride the revenge trail with Wyatt and Doc. Hide in the shadows hoping your young bride can clear your name. Make the perilous journey through Apache country from Fort Huachuca to anywhere. BETWEEN HELL AND TOMBSTONE will grab you with a iron grip and shake you like a dog with a bone. Just try to put it down."--Back cover.